The Effectiveness Of Spiritual Emotional Freedom Technique In Reducing The Incidence Of Postpartum Blues In Pregnant Women - Rahma Zakia Mubarok; Irma Finuria Mustikawati; Paramita Septianawati; Glorio Immanuel (Jurnal Health Sains, 2024)
Despite the joy of being pregnant, some mothers experience anxiety and depression after giving birth. Blues Depression and anxiety throughout pregnancy and after have a significant negative influence on pregnant women's mental health. This research reviewed the available literature. Electronic databases, including Pubmed, Google Scholar, and ProQuest, were used for the searches. Journals containing the terms "Spiritual Emotional Freedom Technique (SEFT)," "Postpartum Blues," "Pregnant Women," and "Pregnancy" were found in the first search. The study's findings indicate that spiritual practices like dhikr and mutual Al-Qur'an, as well as faith-based treatment and spiritual beliefs, have the ability to lessen pregnant women's anxiety and despair.  This study intends to find out if Spiritual EFT could be a useful option for reducing symptoms of postpartum blues, a psychological illness that can impact a woman's emotional health after childbirth. The findings of the study indicate that using this therapy can significantly improve the mental health of expectant mothers.